Ответ:
Пошаговое объяснение:
3. б)5/12(4.8x - 1.2y) - 3.6(2/9x + 7/12y) = 24x/12 - 6y/12 - 7.2x/9 - 25.2y/12= 2x - 0.5y - 0.8x - 2.1y= 1.2x - 2.6y4.1 1/9(3x-9) - 2 1/3(x - 1.8)= 10x/3 - 10 - 7x/3 + 7*0.6= 3x/3 -10 + 4.2= x - 5.8при x=0.75:0.75 - 5.8 = -5.05
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
3. б)
5/12(4.8x - 1.2y) - 3.6(2/9x + 7/12y)
= 24x/12 - 6y/12 - 7.2x/9 - 25.2y/12
= 2x - 0.5y - 0.8x - 2.1y
= 1.2x - 2.6y
4.
1 1/9(3x-9) - 2 1/3(x - 1.8)
= 10x/3 - 10 - 7x/3 + 7*0.6
= 3x/3 -10 + 4.2
= x - 5.8
при x=0.75:
0.75 - 5.8 = -5.05